INFLUENCES OF ORGANIC AND INTEGRATED NUTRIENT MANAGEMENT ON PHYSICO-CHEMICAL PROPERTIES OF SOIL UNDER BASMATI-WHEAT CROPPING SEQUENCE - S. SINGH,; Z. A. BHAT,; H. U. REHMAN, (The Bioscan, 2014)
The present study entitled “Influences of organic and integrated nutrient management on physico-chemical properties of soil under basmati-wheat cropping sequence” was carried at Punjab Agriculture University, Farm on basmati-wheat sequence. The experimental treatments consisted of inorganic fertilizers, organic manures and integrated nutrient management. The cumulative infiltration ranged from 0.9 to 2.4 cm after 1 min under different treatments, the value being highest (2.4 cm after 1 min) in treatments receiving organic manures alone, recommended fertilizer + 200 kg N ha-1 from FYM (1.3 cm after 1 min) than control (0.9 cm after 1 min) and RF alone (1.1 cm after 1 min). The highest values of Soil organic carbon (0.6 %), mineral nitrogen (79.5 mg ha-1), ammonium acetate extractable potassium (145.8 mg kg-1) and bray-I Phosphorus (22.0 mg kg-1 ) in surface soil were recorded in plots receiving 400 kg N ha-1 from vermicompost (VC), rice straw compost (RSC) and farm yard manure (FYM) respectively, which was significantly higher than control, recommended fertilizer alone or in combination with chemical fertilizers (the values in latter i.e RF + FYM being significantly higher than former two treatments i.e control and RF) but at par with other organic treatments, the value of all the four parameters decreased with the depth of profile. The lowest value of bulk density (1.40 gm cm-3), soil pH (5.8) and Soil EC (0.11) in surface soil were observed in the plot where N from FYM at 200 kg ha-1 was applied in combination with recommended fertilizer, 400 kg N ha-1 from FYM and 400 kg N ha 1 from VC respectively, the value of B.D. and soil pH increased whereas that of EC decreased with the soil depth. However crop yield was significantly higher in treatments where RF along with FYM was used than organically treated plots. Thus best alternative for sustaining the soil fertility without compromising the productivity is to use inorganic fertilizers along with the organic manures.